EVALUASI GALUR JAGUNG SMB-5 HASIL SELEKSI MASSA VARIETAS LOKAL BALI ”BERTE” PADA DAERAH KERING - Ni Luh Made Pradnyawathi (Environmental Research Center (PPLH) of Udayana University, 2012)
TThe aimed of this study was to know agronomic characters performance of SMB-5 line mainly yield potential, compared to another local varieties in an arid area. The study was conducted at Sumber Klampok Buleleng in 2007. Randomized Block Design was used, seven varieties i.e. : SMB-5 line (Bt), Seraya (Sr), Cicih Tombong (Ct), Pulut Putih (Pp), Lombok Putih (Lp), Tongtongan Tianyar (Tt), and Ketokong (Kt) as a treatment with three replications. Ninety plants were taken as a random sampling from every genotype. Quantitative characters of SMB-5 line and another varieties tested showed a significant different for more variables except for maximum leaf number, time of tasseling, time of silking, number of productive pods and harvest index. SMB-5 line and another varieties tested was different in genetics showed by a high heritability (h2 > 0.50), and some others showed a main heritability (h2 >0.20). SMB-5 give the highest yield (4.02 ton/ha) which are significant different from another local varieties. SMB-5 lines have a good adaptation potential to an arid area.